PERAN KEPALA MADRASAH DALAM MENINGKAN MUTU PEMBELAJARAN DI MADRASAH ALIYAH - Erfiyana, Evi; Sulaeman, Devi; Kartika, Ika; Arifudin, Opan; Mayasari, Annisa (Penerbit Lafadz Jaya, 2026)
This study aims to describe the role of the madrasah principal in improving the quality of learning in Madrasah Aliyah. The approach used is qualitative with descriptive study methods in several Madrasah Aliyah in region X. Data were collected through in-depth interviews, observations, and documentation to obtain a comprehensive picture of the role of the madrasah principal in managing and facilitating the improvement of the quality of learning. The results of the study indicate that the madrasah principal has a central role in designing policies, motivating teachers, and supervising the learning process to ensure it runs effectively and efficiently. In addition, the madrasah principal plays a role in improving teacher competency through training and supervision, as well as building a conducive learning atmosphere for students. The conclusion of this study is that the success of improving the quality of learning is highly dependent on the leadership of the madrasah principal who is innovative, communicative, and able to manage resources optimally. This study contributes to the development of madrasah leadership theory and becomes an important input for policy makers in improving the quality of education in Madrasah Aliyah.